2021
DOI: 10.2106/jbjs.20.02172
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Rates of Reoperation and Revision Following Mobile Versus Fixed-Bearing Total Ankle Arthroplasty

Abstract: Background:Currently, the implants utilized in total ankle arthroplasty (TAA) are divided between mobile-bearing 3-component and fixed-bearing 2-component designs. The literature evaluating the influence of this mobility difference on implant survival is sparse. The purpose of the present study was therefore to compare the short-term survival of 2 implants of similar design from the same manufacturer, surgically implanted by the same surgeons, in fixed-bearing or mobile-bearing versions.Methods:All patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A recent study reported the short-term rates of reoperation and revision of both mobile-bearing Salto Talaris (Tornier and Integra) and fixed-bearing Salto Talaris (Integra) systems after 3 years. The authors reported a 3 times higher rate of revision among mobile-bearing implants compared with fixed-bearing implants 3 years postoperatively, 1 suggesting that fixed bearing might be superior to mobile bearing in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the short-term rates of reoperation and revision of both mobile-bearing Salto Talaris (Tornier and Integra) and fixed-bearing Salto Talaris (Integra) systems after 3 years. The authors reported a 3 times higher rate of revision among mobile-bearing implants compared with fixed-bearing implants 3 years postoperatively, 1 suggesting that fixed bearing might be superior to mobile bearing in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,12,24 Because the mobile-bearing device was developed and used first in Europe, earlier survival studies used this version of the Salto TAA. Assal et al 1 compared the mobile- and fixed-bearing versions of the Salto implant and found the revision rate to be 3 times higher in the mobile-bearing group at 3-year follow-up. Our results demonstrate improved retention rates in comparison to the mobile-bearing version of this implant.…”
Section: Discussionmentioning
confidence: 99%
“…Assal et al 25 compared 171 patients who underwent mobile-bearing ankle arthroplasty (Salto) with 131 patients who underwent fixed-bearing ankle arthroplasty (Salto Talaris). The study strengths included a relatively large series comparing implants of similar design from the same manufacturer and implanted by the same 2 surgeons, with no patients lost to follow-up.…”
Section: Arthroplastymentioning
confidence: 99%